Current Practices and the Future of Continuous EEG Monitoring in Indian ICUs: Insights from a National Survey - Sachin,; Verma, Archana; Khan, Sharukh; Suri, Madhav (Nepal Journal of Neuroscience, 2025)
Introduction: Continuous electroencephalography (cEEG) is essential for detecting non-convulsive seizures, status epilepticus, and tracking brain activity in critically ill patients. However, its utilization in Indian intensive care units (ICUs) varies. The purpose of this study is to evaluate current cEEG procedures, identify implementation challenges, and investigate the role of remote monitoring in improving patient care in intensive care units.Materials and Methods: In September 2024, a national survey was undertaken in Indian hospitals to assess cEEG prevalence and practices. The poll, which was circulated using Google Forms, was aimed at neurologists, neurophysiologists, intensivists, and EEG technicians. It included 20 questions about hospital characteristics, cEEG availability, use, clinical applications, and barriers. To compare public and private hospitals, data were examined using descriptive statistics and Chi-square/Fisher's exact tests.Results: There were 76 answers, with 63% of ICUs employing cEEG. Private hospitals received 50% of the responses, followed by government hospitals with 38%. Non-convulsive seizures (29%) and status epilepticus (29%) were the predominant reasons for cEEG. Barriers to adoption included a lack of skilled personnel (32%), as well as high expenses (14%). Remote EEG monitoring was employed in 37% of ICUs; however it faced problems such as unstable internet and staff opposition. Despite these challenges, 49% of respondents reported better patient outcomes using cEEG.Conclusion: Although cEEG use is increasing in major Indian institutions, problems remain. Remote monitoring could reduce obstacles and improve access, but consistent training and national guidelines are required to increase cEEG implementation in Indian ICUs.